A Micropragmatic Analysis of Personal and Discourse Deixis in Von der Leyen at the Summit of World Leaders (Zien Journal of Social Sciences and Humanities, 2022)
This pragmatic study strives to investigate how the personal and discoursal deixis of Von der Leyen’s speech in the conference of world leaders on climate change are represented. It is hoped that the study uncovers these concepts through the use of language. As a result, the researchers employ a quantitative-qualitative approach of analysis depending on Levinson’s (1983) model of deixis distribution in the selected utterances. The researchers select the speech of Von der Leyen to be under scrutiny. The findings of the quantitative analysis show that personal deixis are more frequent than discourse deixis by (65%). It also shows that “we” is the most commonly used personal pronoun by (48%). As for the qualitative analysis, it is found that introducing the personal deixis indicate solidarity among the whole nations to protect the world from the environmental crisis.